Lectin nanoparticle assays for detecting breast cancer-associated glycovariants of cancer antigen 15-3 (CA15-3) in human plasma - Joonas Terävä; Leena Tiainen; Urpo Lamminmäki; Pirkko-Liisa Kellokumpu-Lehtinen; Kim Pettersson; Kamlesh Gidwani (Public Library of Science, 2022)
Cancer antigen 15–3 (CA15-3) is widely utilized for monitoring metastatic breast cancer (BC). However, its utility for early detection of breast cancer is severely limited due to poor clinical sensitivity and specificity. The glycosylation of CA15-3 is known to be affected by BC, and therefore it might offer a way to construct CA15-3 glycovariant assays with improved cancer specificity. To this end, we performed lectin-based glycoprofiling of BC-associated CA15-3. CA15-3 expressed by a BC cell line was immobilized on microtitration wells using an anti-CA15-3 antibody. The glycosylation of the immobilized CA15-3 was then detected by using lectins coated onto europium (III)-doped nanoparticles (Eu+3-NPs) and measuring the time-resolved fluorescence of Eu. Out of multiple lectin-Eu+3-NP preparations, wheat germ agglutinin (WGA) and macrophage galactose-type lectin (MGL) -Eu3+-NPs bound to the BC cell line-dericed CA15-3 glycovariants (CA15-3Lectin). To evaluate the clinical performance of these two lectin-based assays, plasma samples from metastatic BC patients (n = 53) and healthy age-matched women (n = 20).Plasma CA15-3Lectin measurements better distinguished metastatic BC patients from healthy controls than the conventional CA15-3 immunoassay. At 90% specificity, the clinical sensitivity of the assays was 66.0, 67.9 and 81.1% for the conventional CA15-3, CA15-3MGL and CA15-3WGA assays, respectively. Baseline CA15-3MGL and CA15-3WGA were correlated to conventional baseline CA15-3 levels (r = 0.68, p<0.001, r = 0.90, p>0.001, respectively). However, very low baseline CA15-3MGL levels ≤ 5 U/mL were common in this metastatic breast cancer patient population.In conclusion, the new CA15-3Lectin concept could considerably improve the clinical sensitivity of BC detection compared to the conventional CA15-3 immunoassays and should be validated further on a larger series of subjects with different cancer subtypes and stages.